PRACTICE OF DOCUMENTATION AT CASUALTY OF TERTIARY CARE HOSPITAL – AN INTERVENTIONAL STUDY (Medico Legal Update, 2021)
A medical record plays a major role for the patient and health care sector in terms of treatment and makingpolicies on certain diseases. In any suit of negligence, this medical record will help the doctors to defendthem. Many a times the complete and accurate documentation only have helped the medical fraternitiesfrom getting entangled in various consumer cases made by the patient against the doctors. Even though wehave seen so many negligence cases on doctors, documentations are still incomplete in any medical record.There are studies shown that the average time spent by a doctor on a medical record is very less and thescenario is much worse when it comes to critical areas of the hospitals like casualty where the time is veryprecious in treating the patient and not much of importance is given for documentation. So to identify thecurrent practice of documentation of medical records, this study was carried out to assess the documentationpractice of the admission case sheets in the casualty of SMVMCH, Puducherry. An intervention was doneto improve the completeness of documentation in the casualty and post-intervention analysis was also done.The results of the study showed that the percentage of documentation out of the 34 variables documented inthe admission case sheets found to have significant deficiencies. But following the intervention on improvingthe documentation there has be a significant decrease of the deficiencies in the documentation practice onall those 34 variables.